Bibliometric Analysis of Research Developments In Office Administration - Evi Zakiyah; Santi Dewiki; Al Muhdil Karim (International Journal of Science and Environment (IJSE), 2026)
Phenomena/issues: Office administration is a rapidly growing field and many studies have been conducted related to this field. However, research that discusses the analysis of publications related to this field has not been carried out so that analysis is needed to bibliometric create more targeted research in the future. Objectives: This study aims to contribute to a deeper understanding of the development of research office administrationand to provide clearer direction for future research. Novelty: This research adds an in-depth understanding of the publications to be made in the field of office administration that has not been done in analysisprevious . bibliometric Research Methods: This study uses analysis bibliometric using the Scopus database as the main data source which is then analyzed based on the year of publication, related fields of science, country of publication, and author of publication. The data was then processed using VOSviewer which was analyzed using two visualizations, namely visualization network and density visualization. Results: The results of this study show that there is a significant growth each year in publications on office administration. The United States is the highest country that publishes related research. Keywords that appear in the field of office administration range from medicine to social sciences. The terms that appear are related to other terms with a smaller number of publications. Research Contribution: this research provides a real contribution for researchers who will examine the field of office administration both from the country of the publisher, author, keywords or related terms, to the relationship between these terms to create higher quality research.